High-Expectations Relationships: A Foundation for Enacting High Expectations in all Australian Schools - Sarra, Chris; Spillman, David; Jackson, Cathy; Davis, John; Bray, John (The Australian Journal of Indigenous Education, 2020)
Enacting high expectations for all students in the classroom is a complex undertaking. Underlying, out-of-awareness assumptions may lead to actions, behaviours or pedagogic choices that do not support these high expectations beliefs and intentions. For Indigenous education, this is compounded by public and professional discourses around deficit positioning, and by historical conditioning, where many Indigenous students do not see achieving in school as part of their cultural identity. High expectations are usually considered as a performance agenda — in terms of effort, learning and achievement. In this paper, we introduce the concept of high-expectations relationships where viewing and enacting high expectations through a relational lens equips educators with strategies to support such performance outcomes. We describe this relational lens where fair, socially just relating establishes a relational space of trust, thus enabling both student motivation and the firm, critically reflective relating necessary for quality learning. Using the voices of educators, we describe how high-expectations relationships can promote collegiate staff environments, strong teacher–student relationships and trusting and supportive relationships with parents and carers. We show how these positive educational attributes of any school community, seeded through a focus on high-expectations relationships, work to support the performance outcomes of a high-expectations educational agenda.